1998
DOI: 10.1074/jbc.273.18.11370
|View full text |Cite
|
Sign up to set email alerts
|

Protease Resistance of Syntaxin·SNAP-25·VAMP Complexes

Abstract: A stable ternary complex formed with vesicle-associated membrane protein 2 (VAMP2) and plasma membrane proteins syntaxin 1A and synaptosome-associated protein of 25 kDa (SNAP-25) is proposed to function in synaptic vesicle exocytosis. To analyze the structural characteristics of this synaptic protein complex, recombinant binary (syntaxin 1A⅐SNAP-25), recombinant ternary, and native ternary complexes were subjected to limited trypsin proteolysis. The protected fragments, defined by amino-terminal sequencing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 29 publications
(57 reference statements)
4
68
0
Order By: Relevance
“…3i, amino acids 85-120 of SNAP-25 were sufficient to target a heterologous protein to the plasma membrane of NG108 cells. Interestingly, this sequence coincides almost exactly with the protease-sensitive interhelical domain (residues 83-120) of SNAP-25 in the SNARE complex (11,12). All of the deletion constructs were expressed at similar levels and migrated at the predicted molecular mass as assessed by immunoblotting (data not shown).…”
Section: Full-length Snap-25 Targets Gfp To the Plasma Membrane-snap-25mentioning
confidence: 95%
See 1 more Smart Citation
“…3i, amino acids 85-120 of SNAP-25 were sufficient to target a heterologous protein to the plasma membrane of NG108 cells. Interestingly, this sequence coincides almost exactly with the protease-sensitive interhelical domain (residues 83-120) of SNAP-25 in the SNARE complex (11,12). All of the deletion constructs were expressed at similar levels and migrated at the predicted molecular mass as assessed by immunoblotting (data not shown).…”
Section: Full-length Snap-25 Targets Gfp To the Plasma Membrane-snap-25mentioning
confidence: 95%
“…The cysteine-rich sequence is contained within the linker between the N-and C-terminal helices that SNAP-25 contributes to the core synaptic fusion complex (4). The structure of the linker domain is unknown, but is presumed to be exposed and disordered in the complex in vitro because of its susceptibility to proteolytic cleavage (11,12). In any case, this region of SNAP-25 has to be sufficiently extended to accommodate the parallel orientation of both SNAP-25 helices in the synaptic fusion complex (4).…”
mentioning
confidence: 99%
“…Poirier et al (45) have suggested that SNAP-25 may contribute to SNARE complex oligomerization if its C-terminal ␣-helix participates in a different SNARE complex than its N-terminal ␣-helix. Other proteins that interact with the SNARE complex, such as complexin, or Ca 2ϩ -dependent oligomerization of synaptotagmin also may mediate this function.…”
Section: No Change In Synaptotagmin Expression or Synaptic Localizationmentioning
confidence: 99%
“…Moreover, inclusion of these TMDs increased the stability of the ternary complexes and affected the ability of the cytoplasmic domains to join other proteins (4,5). Co-reconstituted into liposomes, synaptobrevin II and syntaxin 1A formed a stable binary complex that required the presence of the TMDs (6).…”
mentioning
confidence: 99%
“…Analysis of ternary complexes formed by the full-length proteins revealed that the C-terminal transmembrane domains (TMDs) of both Sx1A and synaptobrevin II were protected from trypsin digestion (4). Moreover, inclusion of these TMDs increased the stability of the ternary complexes and affected the ability of the cytoplasmic domains to join other proteins (4,5).…”
mentioning
confidence: 99%